BUSINESS DEVELOPMENT STRATEGY USING SWOT AND AHP METHODS IN NURI SNACK MSMES - Alfiana Restuningsih; Aji Kusumastuti Hendrawan; Siti Fauzatun Wachidah (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
Indonesia's economy is strongly supported by MSMEs which also play a strategic role in increasing the added value of agricultural products such as sweet potatoes, bananas, and cassava. The form of agricultural product management business that is often found is a variety of chips business, one of the business actors is MSME Nuri Snack. The number of various chip business actors, makes business competition and product sales fluctuate. There needs to be a business development strategy in order to survive and win the market. One of them is with SWOT and AHP analysis. SWOT analysis provides an overview of the condition of a business that allows 4 alternative businesses depicted through a quadrant diagram of SWOT analysis. There needs to be a decision-making method to help formulate the best strategy, namely using the AHP Method The results of the Priority Vector calculation from AHP are used as weight values in matrix weighting SWOT matrix weighting obtains IFAS values (X axis = 0.31249977) and EFAS (Y axis = 0.40458977.) which results in an Aggressive Quadrant 1 position with an alternative strategy S-O (using strength to seize the opportunities they have).